PENGARUH PELATIHAN TERHADAP PRILAKU KERJA INOVATIF PEGAWAI DIMEDIASI OLEH SELF-EFFICACY PADA DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI RIAU - Kurniawan, Denny; Rasyid Abdillah , Muhammad; Seswandi, Agus (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of training on innovative work behavior of employees with self-efficacy as a mediating variable at the Energy and Mineral Resources (ESDM) Office of Riau Province. Innovative work behavior is key to improving the performance of public organizations, especially in the era of digital transformation. The study used a quantitative approach with a survey method of 160 ASN employees at the ESDM Office of Riau Province using a saturated sampling technique. Data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results showed that: (1) training had a positive and significant effect on self-efficacy (β=0.829; t=36.015; p<0.001); (2) training had a positive and significant effect on innovative work behavior (β=0.457; t=6.167; p<0.001); (3) Self-efficacy has a positive and significant effect on innovative work behavior (β=0.466; t=6.432; p<0.001); and (4) Self-efficacy mediates the effect of training on innovative work behavior in a positive and significant manner (β=0.386; t=6.181; p<0.001). The research model has very strong predictive relevance (Q²=0.931) and high goodness of fit (GoF=0.75). These findings emphasize the importance of quality training in building employee self-confidence as a foundation for the emergence of innovative work behavior in a bureaucratic environment. Keywords: training, self-efficacy, innovative work behavior, PLS-SEM, ASN employees